2016
DOI: 10.1039/c5ob02211h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient access to conjugated 4,4′-bipyridinium oligomers using the Zincke reaction: synthesis, spectroscopic and electrochemical properties

Abstract: The cyclocondensation reaction between rigid, electron-rich aromatic diamines and 1,1'-bis(2,4-dinitrophenyl)-4,4'-bipyridinium (Zincke) salts has been harnessed to produce a series of conjugated oligomers containing up to twelve aromatic/heterocyclic residues. These oligomers exhibit discrete, multiple redox processes accompanied by dramatic changes in electronic absorption spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 68 publications
0
17
1
Order By: Relevance
“…The 4-n-alkoxyanilines were prepared in accordance with the modified literature procedure [41]. The bis(4-alkoxyphenyl)-4,4-bipyridinium dichloride (EV1Cl, EV6Cl, EV8Cl, EV10Cl, EV12Cl, EV14Cl, EV16Cl, EV18Cl, and EV20Cl) with alkyl chains of different lengths were synthesized as shown in Scheme 1 [42][43][44]. The synthetic route was based on a two-step procedure involving the aromatic nucleophilic substitution between the 1-chloro-2,4-dinitrobenzene and 4,4-bipyridine to give the Zincke salt and its subsequent ANRORC (anionic ring opening and ring closing) reaction with the corresponding 4-n-alkoxyanilines.…”
Section: Synthesis Of Bis(4-n-alkoxyphenyl)-44-bipyridinium Bis(trimentioning
confidence: 99%
“…The 4-n-alkoxyanilines were prepared in accordance with the modified literature procedure [41]. The bis(4-alkoxyphenyl)-4,4-bipyridinium dichloride (EV1Cl, EV6Cl, EV8Cl, EV10Cl, EV12Cl, EV14Cl, EV16Cl, EV18Cl, and EV20Cl) with alkyl chains of different lengths were synthesized as shown in Scheme 1 [42][43][44]. The synthetic route was based on a two-step procedure involving the aromatic nucleophilic substitution between the 1-chloro-2,4-dinitrobenzene and 4,4-bipyridine to give the Zincke salt and its subsequent ANRORC (anionic ring opening and ring closing) reaction with the corresponding 4-n-alkoxyanilines.…”
Section: Synthesis Of Bis(4-n-alkoxyphenyl)-44-bipyridinium Bis(trimentioning
confidence: 99%
“…7, the signals of the bipyridinium units and the ethylene bridges disappeared from the spectra, marking the region of the unpaired spin density. 39…”
Section: Strong Charge Transfer Complexes With Anionsmentioning
confidence: 99%
“…Synthesis of the dimeric series of compounds started with double addition of Zincke salt 5 17 to 3-3'-dimethoxybenzidine (6), which we have shown previously to be a good partner in the Zincke reaction. 9 Addition of 1-chloro-2,4-dinitrobezene to intermediate 7 resulted in the formation of di-Zincke salt 8 which was the common intermediate for the synthesis of the series of di-viologen conjugated systems 2a-h. As can be seen from Table 1, the target di-viologen compounds (2a-2i) were mostly isolated in good yields, although 2c and 2f could not be isolated cleanly under these general reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…7 They are also emerging as key components of functional MOFs including those used for carbon sequestering. 8 Very recently, synthetic and analytical studies of conjugated rod-like viologen containing compounds by our group 9 and by Zhao et al 10 have shown them to exhibit unique redox properties and self-assembly characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation